Use of Multi-Tier Concept Diagnostic Tests in Biology Education: A Systematic Review of the Literature - Tugce Duran; Musa Dikmenli (Journal of Education in Science, Environment and Health)
This study aimed to comprehensively examine the articles in which multi-tier concept diagnostic tests, which are among the alternative assessment methods frequently used in recent years to identify misconceptions, were used in biology education between 2000 and 2022. For this purpose, systematic review steps were followed and summarized in the PRISMA diagram. In this process, four databases (Web of Science, SCOPUS, ERIC, and TR Index) were searched, articles were downloaded, elimination/inclusion criteria were applied, and the full texts of the remaining 71 articles were examined in detail. These articles were analyzed in terms of test type, year of publication, country of application, study group and number of participants, validity and reliability analysis, number of questions in the test and question types according to the test type, and it was revealed which subjects of biology they focused on. As a result of the analysis, it was seen that two-tier tests are mostly used in biology education (62%), followed by three-tier (30%) and four-tier tests (8%). It was seen that the reviewed articles were administered in a total of 21 countries. The subjects of the articles were grouped under 11 themes and 53 codes. Although they are new to the literature and have high validity and reliability, it was seen that especially four-tier concept diagnostic tests were rarely used in biology education. In this context, it was recommended to expand the use of four- and five-tier concept diagnostic tests in biology education.